IoT-Based Automatic Wire Cutting and Stripping Machine for Small-Scale Engineering Industry - Zahran, Muhammad Zarul Zafran; Lias, Jais (Evolution in Electrical and Electronic Engineering, 2023)
In this modern era, there are a lot of technological improvements in wire cutting and stripping. The world is moving rapidly towards an automated or smart mechanism. Although there are many systems, there are some disadvantages in wire cutting and stripping which could operate on their own with a human interface. The conventional method of wire cutting and stripping may not work efficiently in terms of human error, poor performance, and accuracy. When the wire is being cut and stripped manually, the worker tends to make mistakes when measuring the wire as it may not be accurate. The continuous process of cutting and stripping will hurt the worker’s wrist and might lead to a minor injury. In this project, an IoT-based automatic wire cutter and stripper machine were developed to increase the wire cutting and stripping performance. The machine is compared to the conventional method of wire cutting and stripping on the accuracy of measurement and time taken to finish all the processes. Without a human interface, this machine only needs the input of wire length and quantity from the IoT application to operate. The process of wire cutting and stripping will be done automatically and accurately. The machine has shown a more accurate measurement of wire and faster speed of the cutting and stripping process compared to the conventional method by the subjects. The machine will certainly be helpful for small-scale engineering industry that does not have enough budget or big production of wire. This means that this machine is portable, convenient, and easy to use.